2015
DOI: 10.1785/0120140310
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Dynamic Triggered Seismicity in Northern Baja California, México Caused by Large and Remote Earthquakes

Abstract: We analyze the seismicity in northern Baja California, Mexico, that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Their rates rise sharply and then decay over time like aftershocks, although they occur without a local mainshock. These examples demonstrate a globally observed tendency (5,(18)(19)(20)(21)(22) for remotely triggered sequences to be deficient in higher-magnitude earthquakes during the first 24 hours (or longer) as compared with local aftershocks (Fig. 1), which may be a result of comparatively smaller numbers of remotely triggered events or because of a physical process.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Their rates rise sharply and then decay over time like aftershocks, although they occur without a local mainshock. These examples demonstrate a globally observed tendency (5,(18)(19)(20)(21)(22) for remotely triggered sequences to be deficient in higher-magnitude earthquakes during the first 24 hours (or longer) as compared with local aftershocks (Fig. 1), which may be a result of comparatively smaller numbers of remotely triggered events or because of a physical process.…”
Section: Introductionmentioning
confidence: 72%
“…We are primarily interested in learning more about the largest remotely triggered earthquakes because they are the most dangerous. Indications from past studies suggest that these largest events happen but that they are often delayed relative to the arrival of surface waves (18)(19)(20)(21)(22). We begin by carefully examining the earliest observed events in the population of remotely triggered earthquakes as a function of their magnitudes to establish if there are any consistent patterns.…”
Section: It Is Not Difficult To Identify Temporal Associations Betwee...mentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the largest earthquake triggered (M L 3.5) occurred during the passage of the Love-wave peak amplitude. The Chile M w 8.8 earthquake also triggered seismicity in the El Mayor-Cucapah fault, Baja California region, Mexico, where the seismicity increased 10-20 days after this earthquake (Castro et al, 2015).…”
Section: The Central Chile Mw88 Earthquakementioning
confidence: 99%